Yarra Valley Water: double-loop learning and sustainability - Benn, Suzanne (Henry Stewart Talks, 2017)
The case study examines how a water utility company reviewed its approach to sustainability and as a result changed its underlying assumptions about the environment, the water industry, and customer expectations.